A Prospective Clinical Study on MGMT Protein Expression and the Effect of Gene Promoter Methylation on Sensitivity to Chemotherapeutics in Spinal Glioma - Sun P; Fan DJ; Fan T; Li X; Qi XL; Zhao XG; Gai QF (Dove Medical Press, 2021)
Peng Sun,1,* Duo-Jiao Fan,1,* Tao Fan,2 Xin Li,3 Xue-Ling Qi,2 Xin-Gang Zhao,2 Qi-Fei Gai2 1Baoding Second Hospital, Hebei, 071051, People's Republic of China; 2Department of Neurosurgery Spine Center, Sanbo Brain Hospital, Capital Medical University, Beijing, 100093, People's Republic of China; 3Department of Neurosurgery, Baoding No. 1 Central Hospital, Hebei, 071051, People's Republic of China*These authors contributed equally to this workCorrespondence: Tao FanDepartment of Neurosurgery Spine Center, Sanbo Brain Hospital, Capital Medical University, No. 50 Yikesong Road, Xiangshan, Haidian District, Beijing, 100093, People's Republic of ChinaTel +86 010 62856746Fax +86 010 62856902Email fanT064@126.comObjective: The present study discusses the O6-methylguanine-DNA methyltransferase (MGMT) protein expression of spinal glioma cells and the correlation between the sensitivity of promoter methylation of the MGMT gene to chemotherapy drugs, establishes a prediction method for the sensitivity of chemotherapy drugs on spinal gliomas, providing a theoretical basis for determining the best chemotherapy regimens for clinical patients after a spinal glioma operation.Methods: A total of 67 patients, who received microsurgical resection for spinal glioma from October 2010 to June 2016, were selected for the present study. Immunohistochemistry and methylation were performed after the operation. Among these patients, 47 patients with postoperative chemotherapy were assigned as the experimental group, while 20 patients without chemotherapy were designated as the control group.Results: Among the 47 patients in the experimental group, 39 patients had no tumor recurrence after two years, while tumors increased and symptoms were aggravated in eight patients. The progression-free survival rate of chemotherapy was 82.9%, and the two-year survival rate was 100%. The adverse reactions of patients during chemotherapy were slight. Among the 20 patients in the control group, seven patients had no tumor recurrence, while 13 patients had increased tumor size, and the progression-free survival rate was 35.0%.Conclusion: Under the guidance of MGMT immunohistochemical detection and MGMT gene promoter methylation detection after surgery, chemotherapy can effectively delay tumor recurrence, prevent a reoperation, and have good safety and tolerability. This chemotherapy regimen has good prospects.Keywords: spinal cord, glioma, microscopic surgery, chemotherapy, temozolomide